Hmong Americans in Michigan - Bloomfield, Martha Aladjem (Book collections on Project MUSE., 2014)
The Hmong people, originating from the mountainous regions of China, Vietnam, Thailand, and Laos, are unique among American immigrants because of their extraordinary history of migration; loyalty to one another; prolonged abuse, trauma, and suffering at the hands of those who dominated them; profound loss; and independence, as well as their amazing capacity to adapt and remain resilient over centuries. This introduction to their experience in Michigan discusses Hmong American history, culture, and more specifically how they left homelands filled with brutality and warfare to come to the United States since the mid-1970s. More than five thousand Hmong Americans live in Michigan, and many of them have faced numerous challenges as they have settled in the Midwest. How did these brave and innovative people adapt to strange new lives thousands of miles away from their homelands? How have they preserved their past through time and place, advanced their goals, and cultivated plans for their children and education? What are their lives like in the diaspora? As this book documents via personal interviews and extensive research, despite the tremendous losses they have suffered for many years, the Hmong people in Michigan continue to demonstrate courage and profound resilience.